Impact of cesarean delivery due to maternal choice on perinatal outcome in term nulliparous patients with a singleton fetus in a vertex presentation. (2nd November 2022) - Hoffmann, Eva; Vintzileos, William S.; Akerman, Meredith; Vertichio, Rosanne; Sicuranza, Genevieve B.; Vintzileos, Anthony M.
Abstract: Objective: The objectives of our study were to: (1) evaluate the prevalence of cesarean delivery due to maternal request among nulliparous, term, singleton, vertex (NTSV) patients; (2) identify the clinical profile, if any, of these patients; and (3) compare the perinatal outcomes between NTSV patients who requested a cesarean delivery versus patients who did not request cesarean delivery. Study design: This was a retrospective case control study performed at a single institution between November 2018 and July 2019. All NTSV patients who had a cesarean delivery due to maternal choice were identified and compared to the next two NTSV patients in labor who delivered vaginally or by medically indicated cesarean delivery following a cesarean delivery by maternal choice. The primary outcome was composite neonatal morbidity. Secondary outcomes were individual components of composite neonatal and maternal morbidity. Results: Of 1138 NTSV patients, 61 (5.4%) patients opted for cesarean delivery by maternal choice. There were significant differences in the demographic/clinical profile between cases and controls including BMI (35.3 kg/m 2 vs. 32.7 kg/m 2, p < .01), birthweight (3552 gr vs. 3333 gr, p < .001) and documented mental illness (41.0% vs. 22.1% respectively, p < .01). There was no significant difference in composite neonatal morbidity between cases and controls (6.6% vs. 5.7%, adjusted odds ratio [aOR] 0.96, 95% CI 0.25–3.61). The risk for postpartum hemorrhage requiring blood transfusion was higher (but not statistically significant) in the study group (5.0% vs. 0.0%, aOR 6.43, 95% CI: 0.65–63.24). Patients who chose cesarean delivery during the intrapartum period had a higher (but not statistically significant) composite neonatal morbidity (14.3% vs. 5.7%, aOR 2.24, 95% CI 0.52–9.78) and composite maternal morbidity (28.6% vs.11.8%, aOR 2.90, 95% CI 0.92–9.16) and significantly higher transfusion rate (aOR 16.93, 95% CI 1.53–187.74). Conclusion: Cesarean delivery by maternal choice in NTSV patients is not associated with improved neonatal outcomes; in contrast, it is associated with increased composite maternal morbidity and increased transfusion rate.